The Impact of Portuguese Economic and Financial Assistance Program on the Employability of the Azorean Nurse after the Financial Crisis of 2009-2010 - Luis Carlos do Rego Furtado (European Scientific Journal, ESJ, 2022)
The economic crisis that followed the financial crisis that began in the United States of America in 2008 quickly spread to the whole world, leaving structural problems in several countries unveiled, particularly in those that, due to successive deficits and high external indebtedness, were in a more fragile situation. In the Portuguese case, external assistance was needed, made available in exchange for structural reforms and the abrupt, and severe reduction in public expenditure. The applied austerity had repercussions throughout society, but the public sector felt the weight of the used measures concretely, with health services being no exception. The shock waves caused by public expenditure containment policies were particularly felt in the Azores, an ultra peripheral region marked by geographical discontinuity. These are significant asymmetries at various levels from island to island and across several sectors. The public sector is the primary employer. This paper focuses on understanding if the Portuguese Economic and Financial Assistance Program, implemented between 2011 and 2014, affected the employability and dynamics of the labour market of new graduate nurses in the Autonomous Region of the Azores. This quantitative study used descriptive, inferential, and correlation statistics to establish relations with a statistical value between the sample's employability dimensions and the Portuguese Economic and Financial Assistance Program. From the analysis carried out, the study revealed that the restrictions imposed due to the external assistance program led to an increase in precariousness among new graduate nurses and, among other conclusions, a strong contraction in the capacity of hiring nurses by the public health services. As a limitation to the study, there is the need to emphasise that data on unemployment reflected the reality when the questionnaire was applied (May 2019), and the fact that the study did not explore the reasons underlying the unemployment rate found among the participants (although residual).